2005
DOI: 10.7861/clinmedicine.5-1-55
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary hyperaldosteronism assessed by aldosterone/renin ratio and spironolactone testing

Abstract: -Recent studies have suggested that primary hyperaldosteronism may be present in more than 10% of patients with hypertension. We aimed to estimate the prevalence in unselected patients in primary care, and investigate the influence of current drug treatment upon the aldosterone/renin ratio (ARR) and its prediction of blood pressure response to spironolactone. We measured blood pressure, plasma electrolytes, renin activity and aldosterone in 846 patients with hypertension. Spironolactone 50 mg was prescribed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…The starting sample size of 296, however, was comparable to other primary care prevalence studies in which retention of subjects for further screening was low, and prevalence was similar to ours (13,21,22 Using a similar ARR cutoff as our study (ARR ≥ 25), they reported a 7.5% prevalence on screening. Although the prevalence in that study is similarly low to that demonstrated in our population, the U.K. study utilized a more stringent ARR cutoff for screening (ARR cutoff ≥ 40) (23). Other studies in the primary care setting from Sweden, Singapore, and Chile report a PA prevalence between 1.6% and 8.5% (10,22,24,25).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The starting sample size of 296, however, was comparable to other primary care prevalence studies in which retention of subjects for further screening was low, and prevalence was similar to ours (13,21,22 Using a similar ARR cutoff as our study (ARR ≥ 25), they reported a 7.5% prevalence on screening. Although the prevalence in that study is similarly low to that demonstrated in our population, the U.K. study utilized a more stringent ARR cutoff for screening (ARR cutoff ≥ 40) (23). Other studies in the primary care setting from Sweden, Singapore, and Chile report a PA prevalence between 1.6% and 8.5% (10,22,24,25).…”
Section: Discussionmentioning
confidence: 59%
“…performed in limited populations, specifically those with patients referred to subspecialty centers for the management of hypertension. Few studies have endeavored to determine the disease prevalence in the primary care setting (21)(22)(23)(24). Furthermore, screening of patients for PA in general hypertensive populations is often overlooked unless patients have concomitant hypertension and hypokalemia.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Using the renin-mass assay, we were able to define a normal range in measurements on 850 randomly selected patients in primary care, excluding those on confounding drugs. 3 Whereas the detection limit of the renin activity assay lay within the usually quoted normal range (i.e., the lower 5% of levels were undetectable) this is not the case for renin mass assay. This permits recognition of patients in whom renin secretion is suppressed below the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…All three patients had severe resistant hypertension that was reversed by adrenalectomy, with blood pressure (BP) falling to target despite withdrawal of all but one to two drugs. Use of aldosterone-renin ratio (ARR) was first introduced in 1981 3 and has become widely used in recent years as a screening test for primary hyperaldosteronism. However, it does not differentiate between adenoma and bilateral adrenal hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Spironolactone also effectively decreases BP in patients with or without hyperaldosteronism [10][11][12][13][14][15][16][17][18] . Small, uncontrolled studies have also shown its effectiveness in patients with resistant hypertension [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%